The Role of Effectuation in Achieving Competitive Advantage: Testing the Mediating Role of Agility and Innovation Orientation - Maya Faridhotul Aini; Sri Palupi Prabandari; Radityo Putro Handrito (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study examines how smallholder cocoa farmers in Indonesia achieve competitive advantage under high market uncertainty by investigating whether effectuation logic — an expertise-driven, non-predictive decision-making approach — functions as the cognitive foundation for building competitive superiority, and through which internal capability pathways this transformation occurs. Design/Methodology/Approach – A quantitative cross-sectional survey of 260 smallholder cocoa farmers was conducted using purposive sampling across major Indonesian cocoa-producing regions. Data were analyzed using SEM-PLS (SmartPLS 4.0) with 5,000-subsample bootstrapping to test direct and mediation effects. Findings/Results – Effectuation logic does not directly influence competitive advantage but significantly predicts individual agility (β = 0.466, p < 0.001) and innovation orientation (β = 0.202, p < 0.01). Both variables fully mediate the effectuation–competitive advantage relationship, with innovation orientation as the dominant pathway (β = 0.477, p < 0.001). Originality/Value – This study introduces the cognitive-behavioral translation mechanism, establishing that effectuation generates competitive advantage exclusively through behavioral capabilities, not directly. It demonstrates that agility produces a negative competitive effect in buyer-dominated commodity markets challenging universal agility positivity assumptions  and extends dynamic capability theory to individual farmer-entrepreneurs in developing-economy agribusiness.